New Light on Peripheral Akkadian from Qaṭna: Texts between Language and Writing System - Baranowski, Krzysztof J. (Altorientalische Forschungen, 2018)
The linguistic status of Peripheral Akkadian is a complex question. The texts from Qaṭna help to elucidate it. The texts, which underlie these documents, were uttered in Hurrian, while Sumerian, Akkadian and Hurrian constituted complementary writing platforms to record it. Seen in this light, the question of defining the language of these texts is malapropos. Instead, it is necessary to differentiate the status of individual languages. Such an inquiry is historically feasible by adopting second language acquisition as a theoretical framework.